y=-(3-5)^2+3

9 answers

To simplify the expression, we need to follow the order of operations.

1. First, we need to compute the value inside the parentheses: (3-5) = -2

2. Next, we square the result: (-2)^2 = 4

3. Then, we multiply by -1: 4 * -1 = -4

4. Finally, we add 3: -4 + 3 = -1

Therefore, the simplified expression is y = -1.
y=-(4-5)^2+3
To simplify the expression, we need to follow the order of operations.

1. First, we need to compute the value inside the parentheses: (4-5) = -1

2. Next, we square the result: (-1)^2 = 1

3. Then, we multiply by -1: 1 * -1 = -1

4. Finally, we add 3: -1 + 3 = 2

Therefore, the simplified expression is y = 2.
y=-(5-5)^2+3
To simplify the expression, we need to follow the order of operations.

1. First, we need to compute the value inside the parentheses: (5-5) = 0

2. Next, we square the result: (0)^2 = 0

3. Then, we multiply by -1: 0 * -1 = 0

4. Finally, we add 3: 0 + 3 = 3

Therefore, the simplified expression is y = 3.
y=-(6-5)^2+3
To simplify the expression, we need to follow the order of operations.

1. First, we need to compute the value inside the parentheses: (6-5) = 1

2. Next, we square the result: (1)^2 = 1

3. Then, we multiply by -1: 1 * -1 = -1

4. Finally, we add 3: -1 + 3 = 2

Therefore, the simplified expression is y = 2.
y=-(7-5)^2+3
To simplify the expression, we need to follow the order of operations.

1. First, we need to compute the value inside the parentheses: (7-5) = 2

2. Next, we square the result: (2)^2 = 4

3. Then, we multiply by -1: 4 * -1 = -4

4. Finally, we add 3: -4 + 3 = -1

Therefore, the simplified expression is y = -1.